2014
DOI: 10.1111/1348-0421.12110
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus‐6A gQ1 and gQ2 are critical for human CD46 usage

Abstract: Based on genetic and antigenic differences and on their cell tropism, human herpes virus-6 (HHV-6) has been classified into two variants, HHV-6A and HHV-6B. Recently, these variants were re-classified as two different species. The HHV-6A glycoprotein complex, gH/gL/gQ1/gQ2 binds to its cellular receptor, CD46; however, the corresponding complex in HHV-6B rarely binds to CD46. To determine which viral molecules in the glycoprotein complex determine HHV-6A-CD46 binding, each molecule of the HHV-6A complex (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Thus, it could be inferred that the gH and gL subunits of HHV-6A and -6B do not contribute to the binding of the tetrameric complexes to different receptors. On the other hand, the gQ1 and gQ2 subunits of HHV-6A and -6B share relatively low sequence identity (21)(22)(23), and we have confirmed that a chimeric complex composed of gQ2, gH, and gL of HHV-6B and gQ1 of HHV-6A could bind CD46, although at a lower affinity (24). Therefore, it is highly likely that the gQ1 subunit is responsible for the differential receptor binding of the gH/gL/gQ1/gQ2 complexes of HHV-6A and -6B.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Thus, it could be inferred that the gH and gL subunits of HHV-6A and -6B do not contribute to the binding of the tetrameric complexes to different receptors. On the other hand, the gQ1 and gQ2 subunits of HHV-6A and -6B share relatively low sequence identity (21)(22)(23), and we have confirmed that a chimeric complex composed of gQ2, gH, and gL of HHV-6B and gQ1 of HHV-6A could bind CD46, although at a lower affinity (24). Therefore, it is highly likely that the gQ1 subunit is responsible for the differential receptor binding of the gH/gL/gQ1/gQ2 complexes of HHV-6A and -6B.…”
supporting
confidence: 72%
“…We reported previously that the chimeric complex composed of gQ1 and gQ2 of HHV-6A and gH and gL of HHV-6B could bind to CD46 (24). Furthermore, the chimeric complex composed of gQ1 and gQ2 of HHV-6B and gH and gL of HHV-6A could bind to CD134 (13).…”
mentioning
confidence: 97%
“…A similar solution may have been adopted in HCMV with gO and ULs binding to gH/gL to form complexes that assume the functions of receptor binding and fusion regulation. Similar to HCMV, it has been shown that in HHV-6A, the gQ1/gQ2 components of the tetrameric gH/gL/gQ1/gQ2 complex are directly involved in binding to the entry receptor CD46 (45).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been demonstrated that apart from the heterotetramer complex, gB is also essential for the membrane fusion by HHV-6 (Tanaka et al, 2013). Among the components of the heterotetramer, gQ1 and gQ2 seem to play a critical role in binding to CD46 (Jasirwan et al, 2014).…”
Section: Betaherpesvirusesmentioning
confidence: 99%